Conservative management of pregnancy in diabetic women. Issue 6425 (21st April 1984) - Murphy, J; Peters, J; Morris, P; Hayes, T M; Pearson, J F
Abstract : In 1979 the obstetric management of pregnancies in diabetic women in Cardiff was changed from elective delivery at 37-38 weeks to delivery at term. This change was facilitated by home monitoring of blood glucose concentrations and improved techniques for assessing fetal wellbeing. There were 35 pregnancies in insulin dependent diabetics in 1972-8 and 45 in 1979-82. The quality of diabetic control during pregnancy was equally good in both periods. The average gestation at final admission to hospital increased from 30 to 37 weeks. Amniocentesis to assess fetal pulmonary maturity was necessary in 26 patients (74%) in the first period of study and in only four (9%) in the second. Gestational age at delivery increased from 37.4 to 39.4 weeks after the change in policy. The proportion of mothers entering spontaneous term labour and delivering vaginally increased from 14.3% to 37.8%. The mean birth weight of live born, singleton infants increased from 3090 g to 3650 g, the feeding pattern improved, and respiratory problems were less common. Morbidity was reduced and perinatal mortality was not increased with conservative management of pregnancy in diabetic women.